Acquisition Planning for Local Wisdom: Sustaining the Jambi Malay Seloko Tradition through Curriculum Integration - Sampoerno, Mohd. Norma; Nazurty, Nazurty; Kuntarto, Eko; Harjono, Hary Soedarto; Saadah, Maratun; Agustiyara, Agustiyara (FKIP Universitas Jambi, 2026)
This study examines Seloko Adat, a traditional oral tradition of the Jambi Malay community, through the lens of anthropolinguistic pragmatics and language planning. Utilizing a qualitative phenomenological approach, the research analyses Seloko performances across six stages of the wedding ceremony to determine how linguistic structures regulate social interaction and sustain communal identity. Findings reveal that these rituals utilize elaborate metaphors and indirect speech acts to uphold Malay social norms and interpersonal politeness. Pragmatic analysis demonstrates that Seloko serves as a critical mechanism for building inter-family relationships and managing social expectations within the ritual context. However, facing a critical decline in intergenerational transmission, the study explores the pedagogical potential of integrating these linguistic traditions into local curricula as a form of acquisition planning. By documenting this diminishing oral tradition, the research highlights the vital role of ritualized language in maintaining social cohesion and proposes concrete language-in-education frameworks for its curriculum integration to support language revitalization and character development within contemporary Indonesian society.